C-type natriuretic peptide and its precursor: potential markers in human prostate cancer. (March 2015) - Lippert, Solvej; Iversen, Peter; Brasso, Klaus; Goetze, Jens P
Aim: Seminal plasma offer a more organ-specific matrix for markers in prostatic disease. We hypothesized that C-type natriuretic peptide (CNP) expression may constitute such a new target.Methods: Patients with benign prostatic hyperplasia, clinically localized and metastatic prostate cancer were examined for CNP and CNP precursor (proCNP) concentrations in blood and seminal plasma. Furthermore, CNP and the CNP receptor (NPR-B) mRNA contents in tissue from prostate and seminal vesicles were analyzed by qPCR.Results: CNP and NPR-B concentrations decreased with increasing tumor burden (p = 0.0027 and p = 0.0096, respectively). In contrast, seminal plasma CNP and proCNP concentrations were markedly increased with increased tumor burden (p < 0.0001 and p < 0.0001, respectively).Conclusion: CNP/proCNP could be new markers in human prostate cancer.